Non-Substitution Theorems with Durable Capital Goods - Stiglitz, J. E. (Review of Economic Studies, 1970)
Journal Article Non-Substitution Theorems with Durable Capital Goods Get access J. E. Stiglitz J. E. Stiglitz Cowles Foundation Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 4, October 1970, Pages 543–553, https://doi.org/10.2307/2296484 Published: 01 October 1970 Article history Received: 01 August 1968 Revision received: 01 November 1969 Published: 01 October 1970